Family Resource Dilution in Expanded Families and the Empowerment of Married Only Daughters: Evidence From the Educational Investment in Children in Urban China - Wang, Xiaotao; Feng, Xiaotian (Frontiers in Psychology, 2021)
The One-Child Policy dramatically changed the Chinese family structure, and the literature indicates that only children may have an advantage in terms of family resource dilution. Moreover, as Chinese families traditionally prioritize investing in sons, only daughters are found to have been empowered by the policy because they did not need to compete with their brothers for parental investment. However, the literature is limited to only teenage children when they were still living in their parents' homes. It is unclear whether—when the generation of only children grew up and married—their family structure differed from that of children with siblings and whether married only daughters retained more family resources from their parents. Based on the data analysis of a 2016 survey, “Study of Youths in 12 Cities of Mainland China,” including a sample of 1,007 fathers and 2,168 mothers born between 1975 and 1985, this study explores the empowerment of married only daughters, employing the theory of family resource dilution in expanded Chinese families. Using educational investment in children as an example, and with random intercept models, this study presents empirical evidence that the dilution of family resources in Chinese expanded families still benefits males and patrilineal practices. Thus, this study demonstrates that Chinese families still tend to sacrifice the interests of married daughters to ensure support for their adult sons. However, it also illustrates that married only daughters could still connect to their parents' resources, giving them a relatively dominant position for decision-making regarding the family's educational expenditure on her own children. Thus, this study extends our understanding of the family resource dilution theory to Chinese expanded families, underscoring the need for further research on Chinese only children after they marry and form families of their own.